Religion and Folk Belief in Chinese Literature and Theatre - Zhao, Xiaohuan (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This edited volume offers a historical, textual and ethnoanthropological exploration of the meaning and value of religion and ritual and their form and function in relation to Chinese literature and theatre. The term 'theatre' is used here to refer broadly to various types of live performances-theatrical and non-theatrical; sacred and profane- presented in a religious setting, thus including ritual performance and oral performance. Likewise, literature in this volume broadly encompasses both written and oral literatures, including drama, poetry, hagiography, legend, mythology and prosimetric narrative or chantefable for telling and singing. The contributors to the issue draw on a wide range of materials from historical, philosophical and literary texts to field reports and archaeological finds to archived documents and local gazetteers to personal interviews and participant observations. While all the essays are collected under the theme of 'Religion and Folk Belief in Chinese Literature and Theatre', they differ from each other in subject matter, source material and research approach. Rich and varied as they are, these essays fall into two main categories, namely, a historical approach to religion and ritual recorded in (written and visual) texts and an integrated approach that combines historical inquiries into written and visual texts with ethnoanthropological fieldwork on religious rituals and associated performances.